From respect to attention. Evolution of the semantic field of the lexeme atencja - Jastrzębska-Golonka, Danuta (Papers in Linguistics, 2025)
The evolution of language consists in various changes, the most spectacular of which concern lexis. New words and phrases appear, e.g. due to the development of technology, new trends or tendencies to copy items from foreign languages. It seems interesting how the lexeme atencja, which in Old Polish meant szacunek (Eng. respect), started to be used in a new meaning. The modern distribution of the word is the result of neo-semanticization and covers the semantic field of the word uwaga (Eng. attention). Comparative analysis of definitions, semantics, collocations and axiology conducted addressing the collected linguistic material is an attempt to answer the following questions: Can the new form be considered correct?; Is its use legitimate and worth recommending, permissible or definitely not recommended?